For a healthy corral, run, herd or flock [2] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Community-based animal health care in East Africa. Experiences and case studies with particular reference to Kenya